Question time in the Mexican Congress: the rules of the game - Escobar Hernandez, Rosa Margarita (2017)
This study is the first to examine Question Time (QT) in a Latin American congress. Its main goals seek to discover the extent to which QT in the Mexican Chamber of Deputies is different from, or similar to, the House of Commons in the UK Parliament, and if findings and theories of studies conducted on other parliaments apply or not to Mexico’s Congress. A contrastive analysis reveals significant differences in terms of frequency of sessions, rules, and organisation, but not in how oral questions are used to bend the rules of the game. By using the methodology of Discourse Analysis, two QT sessions in the Chamber of Deputies are examined. At a macro-level, the structure of a type of speech referred to as stance-taking delivered by deputies, just prior to the questioning, is examined to identify its genre. At a micro-level, the analysis is on the discourse strategies deputies and government ministers use to interact. Overall, findings and theories on other Westminster-type systems apply to the Mexican Congress. However, the study yields different results compared to other work on parliaments because Mexico has a multi-party system, while in other parliaments there is, basically, a two-party system. Three types of opposition are identified, each one using their own discourse strategies: anti-system, neutral and loyal. While deputies and government ministers play their corresponding assigned roles as questioners and respondents, the analysis shows such roles allow them to do much more than to enquire or to respond, thus using QT for political purposes. Verbal abuse is also examined. Findings show that although the nature of QT is adversarial, when there is a pre-existing familiarity between a deputy and a government minister conflict escalates. What is considered unparliamentary language and the unspoken red lines that have to be crossed for a session to end prematurely differ between the House of Commons in the UK Parliament and Mexico’s Congress.